Perancangan dan Pembuatan Mesin Mixer Adonan Guna Meminimalisir Tingkat Kelelahan Pekerja dengan Pendekatan REBA (Rapid Entire Body Asessment) - Anam, M Khoirul; Satoto, Handy Febri (SURYA TEKNIKA, 2025)
This research was conducted at the UMKM (Micro, Small, and Medium Enterprise) Kerupuk Ayam Bawang Ibu Sunarti. The main issue identified was the inability to meet monthly customer demand due to the semi-automatic mixing process. To address this, a dough mixer machine was designed and developed using anthropometric and REBA (Rapid Entire Body Assessment) methods to improve productivity and reduce workor fatigue.The mixer has a capacity of 75 kg with dimensions of 85 x 85 x 100 cm, designed based on worker body measurements. It uses a double-sided fin blade made of thick stainless steel to ensure durability and hygiene. The machine produces up to 1,935 pieces of kerupuk per day and saves 5 minutes of processing time. Equipped with four wheels for mobility, the machine also lowers worker fatigue from a high to a moderate level based on REBA evaluation.